Perbedaan Coping Stress Mahasiswa di Indonesia dan Malaysia: Differences in Coping with Stress among Students in Indonesia and Malaysia - Nadiya Zakiyyatul Khusna; Dini Rakhmawati; Agus Setiawan (ITScience (Information Technology and Science), 2025)
Academic pressure experienced by students often triggers stress, which impacts psychological well-being and academic performance. This phenomenon occurs in various countries, including Indonesia and Malaysia, with similar educational systems and social cultures. This study focuses on understanding and comparing how students from the two countries manage stress from academic demands. Using a survey method, a quantitative approach was used by distributing the Brief COPE questionnaire to 100 respondents, consisting of 70 students from Indonesia and 30 from Malaysia. Descriptive statistics and independent t-tests were used to analyze the data to test for significant differences between groups. The analysis showed that although Malaysian students showed a slightly higher average score for coping with stress, the difference was not statistically significant. This similarity in coping patterns suggests the influence of cultural background, spiritual values, and similar educational pressures. The results of this study provide relevant information for lecturers, counselors, researchers, and policymakers in designing long-term psychological interventions, stress management training programs, and higher education institution policies that support students' psychological health. Thus, this study also enriches the literature on cross-cultural coping strategies and opens up opportunities for developing higher education approaches more responsive to students' psychosocial challenges in the Southeast Asian region.